Representation of Muslim Women in the Western Media - Nur Latifah Umi Satiti (Jurnal ILMU KOMUNIKASI, 2017)
This essay attempts to argue about the representation of Muslim women in veil in Western media. This topic is chosen because of general discourse about Muslim women, who wear veil as a threat to secular tradition and value of freedom. Besides, media has power to create affirmation about the general discourse. This paper analyses some researches about Muslim women in media. Based on previous research, it can be assumed that media has power to create women representation as otherness and placed them as threat towards secular tradition and value of freedom.